HISTOPATHOLOGY AND SEROLOGY REACTION TO AN IMMUNE COMPLEX INFECTIOUS BURSAL DISEASE VACCINE (V877 STRAIN) IN SPF AND COMMERCIAL BIRDS - MUNIZ, E. C.; RESENDE, M. S.; SILVA, A. F. A.; VERDI, R.; DI FABIO, J.; BORDIN, E. L. (Ars Veterinaria, 2018)
The purpose of this study was to investigate the effect of a new infectious bursal disease (IBD) immune complex vaccine on immune system response in both specific pathogen-free (SPF) and commercial birds. Evaluation of response to the vaccination in the two experiments was done by histopathological examination and serology. The results of this study have shown that immune complex vaccine with the V877 strain is quite safe in White Leghorn SPF birds in which there has been no participation of maternal antibodies. In commercial birds was also observed that the immune complex vaccine with the V877 strain acted synergistically with different levels of passive antibodies and the vaccine virus began to replicate as passive immunity decreased to provide the animal active immunological response.